A Low-Cost National Cooperative Store: The CONZUL Experience. Issue 1 (15th March 2019) - Calvert, Philip
Abstract: The Council of New Zealand University Librarians (CONZUL) has developed a low-cost and pragmatic solution to pressing storage problems. The CONZUL Store is a cooperative agreement between the eight university libraries, which, by using commercial storage, has avoided the huge costs of a new or adapted building. Because all storage is local, lodged items are close enough to make retrieval convenient if necessary. Using several locations spreads the risk of losing everything in a single disaster. To make it possible for items to be moved quickly, CONZUL adopted the process of 'consecutive deposit' in which one library lodged all its items first, made a list of them that was put onto an extranet, and then the second library could safely dispose of duplicate items already deposited and just move the remaining items it wanted to lodge in the Store. The current contract ends in 2023 and at that time it is possible the Store will be closed (this will be reviewed in 2022) because it is likely that many journals will have electronic versions safely archived by publishers or large cooperatives.